Mechanosurveillance: Tiptoeing T Cells - Göhring, Janett; Schrangl, Lukas; Schütz, Gerhard J.; Huppa, Johannes B. (Frontiers in Immunology, 2022)
Efficient scanning of tissue that T cells encounter during their migratory life is pivotal to protective adaptive immunity. In fact, T cells can detect the presence of even a single antigenic peptide/MHC complex (pMHC) among thousands of structurally similar yet non-stimulatory endogenous pMHCs on the surface of antigen-presenting cells (APCs) or target cells. Of note, the extracellular matrix of target cells is bound to affect and even modulate antigen recognition by posing physical barriers composed of proteoglycans and bulky proteins also known as the glycocalyx. T cell-resident microvilli are actin-rich membrane protrusions and puncture through such barriers and place thereby actively the considerably smaller T cell antigen receptors (TCRs) in close enough proximity to APC-presented pMHCs so that productive interactions may occur efficiently yet under force. We here review our current understanding of how the plasticity of T cell microvilli and physicochemical properties of the glycocalyx may affect early events in T cell activation. We finally assess insights gained from studies on T cell plasma membrane ultrastructure and provide an update on current efforts to integrate biophysical aspects such as the amplitude and directionality of TCR-imposed mechanical forces, and the distribution and lateral mobility of plasma membrane-resident signaling molecules into a more comprehensive view on sensitized T cell antigen recognition.